Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan pada Perguruan Tinggi Negeri di Jawa Timur - Pratamasari, Frinta; Muawanah, Umi; Farhan, Djuni (Penerbit Goodwood, 2025)
Purpose: The aim of this research is to find out whether human resource competence, internal control systems and good university governance have a direct or indirect effect on the quality of state universities' financial reports. Methodology/approach: The research uses a quantitative approach, with data collection methods using questionnaires. The research sample was 255 leaders, internal supervisory units, managers and preparers of PTN financial reports in the UAPPA/B Unit in the Java Region. Path analysis was used as an analytical tool in this research, with SEM-PLS. Results/findings: Human resource competency, internal control system and good university governance has a positive and significant effect on the quality of financial reports. Human resource competency and internal control system has a positive and significant effect on good university governance. Human resource competency, internal control system has a positive and significant effect on the quality of financial reports through good university governance. Limitations: This study is limited by measuring the quality of financial reports from the perspective of human resource competency, internal control system and good university governance. While there are several other variables that can affect the quality of financial reports, such as the quality of information technology, because currently financial reports are done based on applications. Contribution: This finding is expected to increase the understanding that quality financial reports are produced by competent human resources in accounting, the organization has good internal control and the organization implements good university governance appropriately. Furthermore, this study contributes to the literature by showing the importance of financial report quality to maintain the image of the organization. Novelty: This study addresses the gap in previous research, that the competence of human resources for managing current financial reports must be complemented by an understanding of the use of applications that have been determined by the ministry.